3D hierarchic interfacial assembly of Au nanocage@Au along with IS-AgMNPs for simultaneous, ultrasensitive, reliable, and quantitative SERS detection of colorectal cancer related miRNAs - Wu, Jiamin; Li, Shengrong; Ma, Yiling; Zhi, Weixia; Chen, Tingting; Huang, Xueqin; Huang, Chan; Zhou, Xia; Zhang, Pengcheng; Zhang, Yuan; Zheng, Guangchao; Wang, Zhigang; et al. (Biosensors & bioelectronics, 2024)
Simultaneous, reliable, and ultra-sensitive analysis of promising miRNA biomarkers of colorectal cancer (CRC) in serum is critical for early diagnosis and prognosis of CRC. In this work, we proposed a novel 3D hierarchic assembly clusters-based SERS strategy with dual enrichment and enhancement designed for the ultrasensitive and quantitative analysis of two upregulated CRC-related miRNAs (miR-21 and miR-31). The biosensor contains the following: (1) SERS probe, Au nanocage@Au nanoparticles (AuNC@Au NPs) labeled with Raman reporters (RaRs). (2) magnetic capture unit, Ag-coated Fe O magnetic nanoparticles (AgMNPs) modified with internal standard (IS). (3) signal amplify probes (SA probes) for the formation of hierarchic assembly clusters. Based on this sensing strategy, the intensity ratio I /I with Lg miRNAs presents a wide linear range (10 aM-100 pM) with a limit of detection of 3.46 aM for miR-21, 6.49 aM for miR-31, respectively. Moreover, the biosensor shows good specificity and anti-interference ability, and the reliability and repeatability of the strategy were then verified by practical detection of clinical serum. Finally, the biosensor can distinguish CRC cancer subjects from normal ones and guide the distinct tumor, lymph node, and metastasis (TNM) stages. Overall, benefiting from the face-to-face coupling of hierarchic assembly clusters, rapid magnetic enrichment and IS signal calibration of AgMNPs, the established biosensor achieves ultra-sensitive and simultaneous detection of dual miRNAs and opens potential avenues for prediction and staging of CRC.